2012
DOI: 10.4067/s0717-95022012000100044
|View full text |Cite
|
Sign up to set email alerts
|

Composición Corporal y Somatotipo de Futbolistas Chilenos Juveniles Sub 16 y Sub 17

Abstract: RESUMEN: El fútbol juvenil, se profesionaliza cada día más, al punto de incluir a los jóvenes en los equipos adultos que juegan en los Torneos Profesionales. Para que esto ocurra es necesario que los jóvenes deportistas estén físicamente aptos para enfrentar las exigencias físicas del futbol profesional. Se evaluó antropométricamente a un total de 217 sujetos distribuidos en dos grupos, sub 16 y sub 17. Los jóvenes futbolistas, presentan diferencias en la estructura corporal con respecto a futbolistas profesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…BC with impedance assessment is commonly used to track the improvement of elite football players throughout the regular season [5]. However, the BC and anthropometric characteristics of young players are little considered in the selection of young football players, as the focus is often placed on the skills that each individual has in their respective specialty [6] or much more time is devoted to increase the physical aptitudes of athletes without taking into account the evaluation of their BC and nutritional status [7], even though we know that there are currently differences in terms of physiological demands according to the position of the player and with respect to their weight, height and body mass index (BMI) [8].…”
Section: Introductionmentioning
confidence: 99%
“…BC with impedance assessment is commonly used to track the improvement of elite football players throughout the regular season [5]. However, the BC and anthropometric characteristics of young players are little considered in the selection of young football players, as the focus is often placed on the skills that each individual has in their respective specialty [6] or much more time is devoted to increase the physical aptitudes of athletes without taking into account the evaluation of their BC and nutritional status [7], even though we know that there are currently differences in terms of physiological demands according to the position of the player and with respect to their weight, height and body mass index (BMI) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is a relatively recent assessment method, there are studies that attempt to define the individual characteristics of players in terms of BC, somatotype and morphological proportionality [3,4]. At present, the BC and anthropometric characteristics of young players are little considered in the selection of young football players, as the focus is often placed on the skills that each individual has in their respective speciality [5] or much more time is devoted to increasing the physical aptitudes of athletes without taking into account the evaluation of their CC and nutritional status [6], even though we know that there are currently differences in terms of physiological demands according to the position of the player and with respect to their weight, height and body mass index (BMI) [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have compared performance in groups of different sports ages in soccer. In this sense, some studies have described body composition, speed, agility, and aerobic endurance as sports performance factors in soccer players in specific stages of training (Benítez Sillero et al, 2015;Calahorro Cañada et al, 2012;Hernando & García García, 2012;Jorquera Aguilera et al, 2012). In addition, these factors have been considered crucial for the search for talent and the specific improvement of the player in his position (Whitehead et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the focus on youth sports ages must be based on developing specific soccer skills and not on the improvement in body composition (Borbón & Alvarado, 2013). However, it is proposed that good muscle development, jump, counterattack, and offensive capacity are the key aspects for the optimal performance of the high-intensity actions required by competitive soccer in adulthood (Jorquera Aguilera et al, 2012;Sánchez Ureña et al, 2011).…”
Section: Introductionmentioning
confidence: 99%